Error-corrected next-generation sequencing mutagenicity assays in human HepaRG cells as human-relevant genetic toxicology new approach methodology - Barutcu, A. Rasim; Bhattarai, Nimisha; Samuel, Raymond; Scaglione, Jamie; Recio, Leslie (Frontiers in Toxicology, 2025)
IntroductionHuman metabolically competent HepaRG™ (HepaRG) cells have been developed as a human-relevant New Approach Methodology (NAM) in genetic toxicology, providing a non-animal alternative to rodent-based mutagenicity testing following a positive Ames test. Error-corrected next-generation sequencing (ecNGS) offers improved sensitivity, specificity, and mechanistic insight in genotoxicity and mutagenicity assessment.MethodsWe applied duplex sequencing, an ecNGS approach, to quantify chemically induced point mutations in metabolically competent HepaRG cells. Cells were exposed to a diverse panel of genotoxic agents, including ethyl methanesulfonate (EMS), N-ethyl-N-nitrosourea (ENU), benzo[a]pyrene (BAP), cisplatin, cyclophosphamide, and etoposide. Mutation frequency, substitution patterns, and mutational signatures were analyzed, and results were compared with complementary cytogenetic endpoints.ResultsDuplex sequencing detected dose-responsive increases in mutation frequency for ENU and EMS, with distinct substitution patterns consistent with alkylating mechanisms. BAP and cisplatin induced modest increases in mutation frequency and C>A-enriched spectra, while cyclophosphamide yielded minimal mutagenicity under the tested conditions. Etoposide triggered strong cytogenetic responses without increasing point mutations, consistent with its clastogenic mode of action. COSMIC mutational signature analysis revealed modest enrichment of SBS4 (BAP), SBS11 (EMS), and SBS31/32 (cisplatin), supporting the mechanistic relevance of the model.DiscussionThese findings demonstrate the reproducibility and specificity of ecNGS for detecting low-frequency point mutations and characterizing mutational mechanisms. When combined with complementary cytogenetic assays, duplex sequencing enables a more complete and human-relevant evaluation of genotoxic potential. This study supports the integration of ecNGS into next-generation genotoxicity testing strategies as a NAM for regulatory decision-making.